How the VA is training the Next‐Generation workforce for learning health systems. Issue 4 (16th August 2022) - Kilbourne, Amy M.; Schmidt, Joel; Edmunds, Margo; Vega, Ryan; Bowersox, Nicholas; Atkins, David
Abstract: Objectives: The U.S. Department of Veterans Affairs (VA) has been a national leader in Learning Health System (LHS) implementation due to its combined mission of research, education, clinical care, and emergency preparedness. We describe the current VA LHS training ecosystem within the Veterans Health Administration's Office of Academic Affiliations (OAA), Office of Research and Development (ORD), ORD's Health Services Research and Development (HSR&D) program, and Innovation Ecosystem (IE), including lessons learned regarding their sustainment. Methods: The VA LHS training ecosystem is based on the Learning Loop and HSR&D Quality Enhancement Research Initiative (QUERI) Roadmap, which describes VA learning opportunities, underlying infrastructures, and core competencies. Results: VA‐focused LHS educational programs include data‐to‐knowledge initiatives in health sciences and analytics, for example, OAA/HSR&D health services and informatics research fellowships; knowledge‐to‐performance opportunities in implementation and quality improvement, for example, QUERI Learning Hubs and IEs' Diffusion of Excellence Initiative; and performance‐to‐data embedded opportunities, for example, IE's entrepreneur fellowship programs and QUERI's Advancing Diversity in Implementation Leadership. These training programs are supported by combined VA research and clinical operations investments in funding, informatics, governance, and processes. Lessons learned include ongoing alignment of research funding with operational priorities and capacity, relentless recruitment and retention of implementation, system, and information scientists especially from under‐represented groups, sustainment of data infrastructures suitable for research and quality improvement, and ensuring sustainable funding opportunities for researchers to work on system‐wide health care problems. Conclusions: There is an urgent need to expand training opportunities in LHSs, especially as health care is increasingly driven by multiple interested parties, impacted by persistent health disparities exacerbated by emerging public health threats, and rapid technology growth. With ongoing alignment of research and clinical goals, foundational support through research funding, underlying clinical operations infrastructures, and active engagement interested parties, VA's LHS training ecosystem promotes a more LHS‐savvy, 21st century workforce.